Exploring the complexity of partnerships in development policy and practice: Upstairs and downstairs. (6th April 2020) - den Heyer, Molly; Johnson, Dustin
Abstract: Motivation: The term partnership, and the balance of ownership within it, significantly influence the direction of the development field and whether it will be able to address increasingly complicated global challenges such as climate change, peace and security and growing inequality. Purpose: The article explores the nature of government donor–recipient partnerships, the struggle over ownership, and the possibility of transitioning from top‐down aid policy to genuine development co‐operation. Approach and Methods: The discussion is based on the lead author's doctoral research and the authors' experiences of working with the Coady International Institute and the Roméo Dallaire Child Soldiers Initiative. Findings: The research revealed ample evidence that proclamations of more equitable partnerships or recipient ownership of aid policy are undermined by historical power dynamics and coherency to dominant development narratives. However, a closer examination also found some room to create change as policy is negotiated and interpreted in a multitude of smaller policy spaces, including influences from networks of civil society organizations (CSOs). The article looks at two CSOs that use their "downstairs" position to act as interlocutors with Southern partners. In some cases, they fostered more equitable partnerships and support South–South networks by applying an emancipatory learning approach and adapting aid modalities. This points to the potential for slow—and often reluctant—progress towards more equitable global partnerships and innovative practices. Policy Implications: The findings suggest that the asymmetrical nature of government donor–recipient partnerships can be addressed through a more nuanced learning approach and increased engagement with CSOs that can experiment with project modalities and support for CSO networks.